2021
DOI: 10.1007/s43678-021-00178-9
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary uses of trauma video review: a scoping review

Abstract: Objectives Trauma resuscitations are sporadic, high-acuity situations and conducting observation in the trauma bay for the purpose of quality improvement is challenging. We aim to review contemporary uses of trauma video review. Methods Medline and Embase were searched from 1980 to May 2020 for studies involving trauma video review. English studies of adult and paediatric populations were included for study and analysed for uses of trauma video review, outcomes measured and any resulting quality improvement (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 40 ] The findings of our review provide more clarity on the use of T-NOTECHS as a standardised tool which would enable use of video review as a tool in education and quality improvement. [ 41 ] One study translated T-NOTECHS into Finnish to assess translatability and validity and found that it can still be used to assess efficacy of trauma team resuscitations. This study used simulated trauma resuscitations, which was an exclusion criteria for our review.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] The findings of our review provide more clarity on the use of T-NOTECHS as a standardised tool which would enable use of video review as a tool in education and quality improvement. [ 41 ] One study translated T-NOTECHS into Finnish to assess translatability and validity and found that it can still be used to assess efficacy of trauma team resuscitations. This study used simulated trauma resuscitations, which was an exclusion criteria for our review.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma video review is increasingly being used for quality improvement and education. 49 Introducing a video review program is not an insurmountable feat, as studies have clearly articulated the salient considerations and challenges of implementing trauma team video review programs at their respective institutions through a legal and ethical lens. 50,51 Video review technology incurs several advantages to comprehensively assess trauma team performance over in-person observation.…”
Section: Using Trauma Video Review To Assess Trauma Team Performancementioning
confidence: 99%
“…For instance, costs, lack of personnel, importance of support, medicolegal concerns, patient privacy and managing data. (13,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) Studies on how to successfully implement and set up the structure for videore exivity in an emergency care department such as neonatology are lacking.…”
Section: Introductionmentioning
confidence: 99%